Synthetic Biology The technoscience and its societal consequences - Schmidt, Markus.; Kelle, Alexander.; Ganguli-Mitra, Agomoni.; Vriend, Huib. (Springer Netherlands, 2010)
Synthetic biology is becoming one of the most dynamic new fields of biology, with the potential to revolutionize the way we do biotechnology today. By applying the toolbox of engineering disciplines to biology, a whole set of potential applications become possible ranging very widely across scientific and engineering disciplines. Some of the potential benefits of synthetic biology, such as the development of low-cost drugs or the production of chemicals and energy by engineered bacteria are enormous. There are, however, also potential and perceived risks due to deliberate or accidental damage. Also, ethical issues of synthetic biology just start being explored, with hardly any ethicists specifically focusing on the area of synthetic biology. This book will be the first of its kind focusing particularly on the safety, security and ethical concerns and other relevant societal aspects of this new emerging field. The foreseen impact of this book will be to stimulate a debate on these societal issues at an early stage. Past experiences, especially in the field of GM-crops and stem cells, have shown the importance of an early societal debate. The community and informed stakeholders recognize this need, but up to now discussions are fragmentary. This book will be the first comprehensive overview on relevant societal issues of synthetic biology, setting the scene for further important discussions within the scientific community and with civil society.